Burnout syndrome among COVID-19 vaccinators - Purwandari, Retno; Ardiana, Anisah; Afandi, Alfid Tri; Kurniawan, Dicky Endrian (Intelektual Pustaka Media Utama, 2023)
Vaccinators, who are health workers, are continuing to make efforts to accelerate the achievement of the COVID-19 vaccination. This study aimed to analyze burnout syndrome among vaccinators. An analytical descriptive with a cross sectional approach was used. The number of samples using G*Power obtained 138 samples with the criteria of health workers who had been on the COVID-19 vaccinating team from public health centers (Puskesmas) and hospitals in Jember, Indonesia. The instrument used in this study was demographic data, factors causing burnout syndrome, and burnout syndrome. The statistical test is a correlative analysis (Spearman's rho, =0.05). Most of the respondents were aged 31-40 years, the majority were women, the majority were married, most came from the Puskesmas, more than half had worked >10 years, and more than half had been on the COVID-19 vaccine team for >18 months. There is a significant relationship between individual effort (p=0.039, r=-0.176) and organizational effort (p=0.009, r=-0.220) with burnout syndrome. However, the work environment was not significantly related to burnout syndrome (p=0.146, r=-0.124). Efforts are needed to reduce the incidence of burnout, especially those related to increasing individual welfare and significant organizational support so that the target for the COVID-19 vaccination is achieved.